The Romance of Leonardo da Vinci, the Forerunner - Merezhkovsky, Dmitry Sergeyevich, 1865-1941; Trench, Herbert, 1865-1923 (Salt Lake City, UT : Project Gutenberg, 2015)
"The Romance of Leonardo da Vinci, the Forerunner" by Dmitry Sergeyevich Merezhkovsky is a novel first published in 1900. Set during the Renaissance, it follows young artist Giovanni Beltraffio as he studies under the master Leonardo da Vinci, struggling to understand why he cannot match his teacher's genius. Against a backdrop of conflict and tragedy, the novel explores the era's re-emerging humanism and the resurrection of ancient values, contrasting the spirit of Antiquity with medieval darkness. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Romance_of_Leonardo_da_Vinci
Release date is 2015-01-10
E-text prepared by Katie Hernandez, Shaun Pinder, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Biographical fiction; Italy -- Fiction; Artists -- Fiction; Leonardo, da Vinci, 1452-1519 -- Fiction